Persepsi pekerja bukan eksekutif terhadap keberkesanan program latihan sambil kerja di sebuah hotel terkemuka di Kuching, Sarawak. - Catherina, ak. Nelson Kuntik. (Universiti Malaysia Sarawak, (UNIMAS), 1999)
The aim ofthis study was to determine the factors that influence non-executive employees' perception toward the effectiveness of on-the-job training program at a hotel in Kuching, Sarawak. The independent variable in this study was the non-executive employees' perception toward on-the-job training program. There were two groups of independent variables in this study, namely, selected demographic factors (gender, age, race, level of education and monthly salary) and organisational culture (supervision, rewards, warmth and support and working condition). A total of 60 respondents were chosen by using simple random sampling and data collection was done by distributing questionnaires to the respondents. The t-test revealed that there is no significant difference between male and female in term of their perception. One-way ANOVA test showed that there is no significant difference among respondents with different sociodemographic characteristics (age, race, level of education and monthly salary) in terms of perception. Pearson Correlation 'r' was done to determine the relationship between organisational culture with non-executive employees' perception. It showed that only warmth and support have significant relationship with non-executive employees' perception. Meanwhile, the other three factors did not show any significant relationship with non-executive employees' perception. Multiple regression showed that warmth and support was the most dominant factor which contributed 10 percent of variance towards overall non-executive employees' perception. Overall, 90 percent ofthe respondents agreed that on-the-job training program in the hotel has been carried out effectively, while 10 percent otherwise. Based on the above findings, it can be concluded that the management of organisation should give attention to warmth and support in order to implement an effective on-the-job training program. It is suggested that future researchers do a comparative study on other hotels to determine the difference in non-executive employees' perception and the factors that influence the perception.